Avaliação cardiovascular para segurança durante a prática de exercícios em indivíduos com condições de saúde respiratórias crônicas - Lima, Vanessa Garcia de (2023)
Introduction: Individuals with respiratory health conditions, such as chronic obstructive pulmonary disease (COPD), asthma, and even COVID-19, may experience physical and functional impairments that can pose risk factors for adverse events during physical exercise, such as blood pressure spikes and orthostatic hypotension. Assessing these risk factors is crucial for the safe implementation of physical exercise in these disease populations. Objective: To analyze risk factors for cardiovascular adverse events during physical exercise in individuals with chronic respiratory health conditions during the pre-participation evaluation in an exercise rehabilitation program. Methods: A cross-sectional observational study was conducted with individuals seeking to participate in an exercise rehabilitation program offered by a public university. Individuals aged 18 and above with a confirmed diagnosis of a chronic respiratory condition, limiting symptoms in daily activities, and the ability to walk and participate in the proposed program were included. Individuals who did not complete the initial evaluation were excluded from the analysis. Sociodemographic and clinical information, risk factors for adverse events during exercise, health-related quality of life, and functional exercise capacity were collected. Questionnaires for cardiovascular symptoms and comorbidities, as well as objective assessments such as a detailed systemic blood pressure (BP) measurement (simultaneously in both arms at least three times) and the presence of orthostatic hypotension (BP after five minutes in the supine position and after one and three minutes standing) were used. Results: Forty-two individuals were evaluated, including 28 (67%) women, with a mean age of 53±18 years. The most prevalent respiratory health condition was post-COVID-19, affecting 16 (38%) individuals. Hypertension was the most frequent cardiovascular condition (38%), but symptoms of cardiovascular conditions were reported by up to 76% of the sample. Among the evaluated participants, 85% achieved reproducible BP results with only three measurements, and the difference between the last two measurements ranged from 1.10 to 1.83 mmHg for systolic BP (SBP). A statistically significant difference was observed only between the penultimate and last measurements of diastolic BP (DBP) in the right arm. Considering the average of the last two measurements, it was observed that in 22 (55%) individuals the SBP was higher in the right arm, while in 18 (45%) it was higher in the left arm. Regarding the distribution between dominant and non-dominant arms, 19 individuals (47.5%) had the highest SBP in the dominant arm, while 21 individuals (52.5%) had it in the non-dominant arm. The difference in SBP between the measurements with the complete protocol versus only one measurement in one of the arms was -2.2 (95% CI -4.2 to -0.2) mmHg. Only one individual (3%) met the criteria for orthostatic hypotension. Conclusions: The presence of signs and symptoms of cardiovascular conditions is common in individuals with chronic respiratory conditions during the pre-participation evaluation of an exercise rehabilitation program, and repeated BP measurements appears to be unnecessary in this scenario.